Haemagalactia Associated with Multidrug Resistant Streptococcus Agalactiae in a Crossbred Holstein Friesian Cow - Azhar, D; Janus, A; Deepa, P.M; Bipin, K.C; Biju P. Habeeb; Remya, V (The Indian Veterinary Journal, 2024)
A recently calved three-year old Holstein Friesian crossbred cow was presented with the complaint of blood in milk from all four quarters. Clinical examination revealed slight swelling and pain of the udder. Haemato-biochemical parameters of the cow were within the normal range except a low serum calcium. Streptococcus agalactiae was isolated from all the four quarters based on Gram stained morphology, cultural characteristics, biochemical tests and PCR. Multi-drug resistance and bio film formation of the isolate was identified. The animal was treated with Ceftriaxone-tazobactum, tranexamic acid, meloxicam and calcium borogluconate and an uneventful recovery was observed.